2020
DOI: 10.3390/ijms21207507
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Induced Functional Alteration of CD4+ and CD8+ T Cells in HNSCC

Abstract: Platelets (PLT) are the second most abundant cell type in human blood and exert various immune-regulatory functions under both physiological and pathological conditions. In fact, immune cell regulation via platelets has been demonstrated in several studies within the past decade. However, the exact mechanisms behind T cell regulation remain poorly understood. We questioned whether the formation of aggregates of platelets and T cells has an impact on T-cell functions. In the present study, we stimulated PBMC cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…Upon activation, platelets can secrete numerous soluble inflammatory mediators and/or bind to leukocytes, thus exerting an immune effect (Rachidi et al, 2017;Zamora et al, 2017;Polasky et al, 2020;Zimmer et al, 2020). In the present study, transwell assays confirmed that the regulation of IFN-g production in T cells…”
Section: Discussionsupporting
confidence: 81%
“…Upon activation, platelets can secrete numerous soluble inflammatory mediators and/or bind to leukocytes, thus exerting an immune effect (Rachidi et al, 2017;Zamora et al, 2017;Polasky et al, 2020;Zimmer et al, 2020). In the present study, transwell assays confirmed that the regulation of IFN-g production in T cells…”
Section: Discussionsupporting
confidence: 81%
“…Activated platelets may associate with T cells in the blood of HIV‐infected individuals (Green et al., 2015 ) and link the coagulation and inflammatory cascade with T cells. In vitro, platelets can inhibit proliferation, cytokine production and PD1 expression of T cells (Polasky et al., 2020 ). Since PMPs derive from platelets, they may also have similar functions as their 'parent’‐platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Activated platelets may associate with T cells in the blood of HIV-infected individuals 68 and link the coagulation and inflammatory cascade with T cells. In vitro , platelets can inhibit proliferation, cytokine production, and PD1 expression of T cells 69 . Since PMPs derive from platelets, they may also have similar functions as their ‘parent’-platelets.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, platelets can inhibit proliferation, cytokine production, and PD1 expression of T cells 69 . Since PMPs derive from platelets, they may also have similar functions as their 'parent'platelets.…”
Section: Pmps Carry Markers Of Activated Plateletsmentioning
confidence: 99%